2009
DOI: 10.5424/sjar/2009074-1107
|View full text |Cite
|
Sign up to set email alerts
|

Compost and vermicompost as nursery pot components: effects on tomato plant growth and morphology

Abstract: Post transplant success after nursery stage is strongly influenced by plant morphology. Cultural practices strongly shape plant morphology, and substrate choice is one of the most determining factors. Peat is the most often used amendment in commercial potting substrates, involving the exploitation of non-renewable resources and the degradation of highly valuable peatland ecosystems and therefore alternative substrates are required. Here the feasibility of replacing peat by compost or vermicompost for the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 37 publications
8
102
0
8
Order By: Relevance
“…However, the application of coffee husk at different sole rates resulted in positive and significant increase in leaf count, stem girth, plant height and leaf area. This is corroborated by some previous results (Rajesh et al, 2003;Veeken et al, 2005;Janvier et al, 2007;Lazcano et al, 2009;Yadessa et al, 2010); amendment of agricultural soils with organic matter as compost resulted in the improvement of the physico-chemical properties of the soil, nutrient release and morphological development of the hosted plants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the application of coffee husk at different sole rates resulted in positive and significant increase in leaf count, stem girth, plant height and leaf area. This is corroborated by some previous results (Rajesh et al, 2003;Veeken et al, 2005;Janvier et al, 2007;Lazcano et al, 2009;Yadessa et al, 2010); amendment of agricultural soils with organic matter as compost resulted in the improvement of the physico-chemical properties of the soil, nutrient release and morphological development of the hosted plants.…”
Section: Discussionsupporting
confidence: 80%
“…Obatolu and Agboola (1991) had reported that cocoa pod husk (CPH) manure contains high Ca, P, K and sizeable amount of useful organic constituents. The use of coffee husk as an organic amendment has been reported and reccommended by Veeken et al (2005), Janvier et al (2007), Lazcano et al (2009) andYadessa et al (2010). According to them, amending agricultural soils with coffee husk as compost supplies plant nutrients and helps to improve the physicochemical and biological properties of the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compost is an organic fertilizer, which is produced by different microorganisms from organic materials (Lazcano et al, 2009). The addition of compost to agricultural soils supplies nutrients and organic matter, decreases leaching of mineral elements from the soil and also improves soil physical structure (Rantala et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…anthocyanin and carotenoids and the variegation appearance can be altered by environmental factors, particularly light intensity (Tilney-Bassett, 1988).House plants provide people with aesthetic appreciation and other beneficial effects. Plants can effectively improve the indoor air quality by reducing volatile organic compounds, such as formaldehyde, benzene, toluene, ethylene, and xylene (Thomsen et al, 2011; Wolverton, 1988), thus reducing the risk of sick building syndrome (Kim et al, 2011).In order to reduce costs and adopt more environmentally-friendly practices, research on alternative substrates is of great interest, and several alternatives have been proposed (Lazcano et al, 2009). The parallel increasing concern in waste recycling has led to the proposal of some organic materials such compost-like substrates (Ostos et al, 2008) In potted plants nowadays soilless media are used as growing media because of its tremendous benefits i.e., good water holding capacity, porosity, aeration and free from water logging conditions and less chances of weed growth, pest and disease infestation.…”
Section: Introductionmentioning
confidence: 99%